The Gene action for morpho-biochemical traits of sesame (Sesamum indicum) in different environments - NEHRA, ANJU; GOTHWAL, D K; JAKHAR, M L; JEETERWAL, RAJESH C; KUNWAR, RAM (The Indian Journal of Agricultural Sciences, 2023)
Sesame (Sesamum indicum L.) is a drought tolerant oilseed crop with the highest oleic acid content, which isyet to be explored for its hybrid vigour. Therefore, present study was carried at Sri Karan Narendra AgricultureUniversity, Jobner, Jaipur, Rajasthan during 2019–20 and 2020–21 to study the combining ability for 11 seed yieldand its attributing traits in 10 parents and their 45 crosses in sesame. The effects of general combining ability andspecific combining ability on morpo-biochemical attributes of cultivars were studied utilizing half-diallel cross. Theexperiment was conducted using randomized blocks design (RBD) with 3 replications under different environmentalconditions. Significant variations were detected among parents for all of the recorded attributes and the F1 generation also showed significant differences for all recorded attributes. The GCA (General Combining Ability)/SCA (Specialized Combining Ability) variance ratio was found to be less than one, indicating that non-additive gene action predominated for all tested attributes. The parents RT–346, TKG–22, RT–372 and RT–351 emerged as good general combiners for seed yield per plant and its attributes in all environmental conditions. The crosses RT–346 × RT–351, TKG–22 × RT–372, RT–372 × RT–351 and RT–103 × RT–351 emerged as good specific cross combinations for seed yield and oil content. Incorporating F1 hybrids with a high SCA and parents with a high GCA into multiple crossings could also to be a beneficial strategy for improving seed production and oil content in sesame.